Severe Disseminated Necrotizing and Granulomatous Lymphadenitis and Encephalitis in a Dog Due to Sporotrichum pruinosum (Teleomorph: Phanerochaete chrysosporium). Issue 2 (March 2018) - Magstadt, Drew R.; Fales-Williams, Amanda J.; Palerme, Jean-Sébastien; Flaherty, Heather; Lindquist, Tracy; Miles, Kristina G.
A 9-year-old female mixed breed dog presented for an acute onset of anorexia, vomiting, and cough. Initial examination and diagnostics revealed a large multilobular cranial mediastinal mass with unidentified fungal organisms on cytology. The disease progressed in spite of therapy until the dog was euthanized 8 months later. Gross necropsy findings were a large multilobular intrathoracic mass, mild pleuritis, and generalized lymphadenopathy. Histologic evaluation showed granulomatous inflammation and necrosis with numerous 20- to 70-micron, periodic acid–Schiff- and Gomori methenamine silver-positive spherules effacing lymph node parenchyma, as well as severe inflammation within the midbrain. Endosporulation was a common finding, and large numbers of fungal hyphae were also present in affected areas. Ribosomal RNA gene sequencing found 100% identity to published sequences of Phanerochaete chrysosporium, the teleomorph form of Sporotrichum pruinosum . This is the first published report of disease caused by natural infection with this basidiomycete organism in animals.